Critical evaluation of oxygen-uptake assessment in swimming - Sousa, A.; Figueiredo, P.; Pendergast, D.; Kjendlie, P.-L.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2014)
Swimming has become an important area of sport science research since the 1970s, with the bioenergetic factors assuming a fundamental performance-influencing role. The purpose of this study was to conduct a critical evaluation of the literature concerning oxygen-uptake (VO2) assessment in swimming, by describing the equipment and methods used and emphasizing the recent works conducted in ecological conditions. Particularly in swimming, due to the inherent technical constraints imposed by swimming in a water environment, assessment of VO2max was not accomplished until the 1960s. Later, the development of automated portable measurement devices allowed VO2max to be assessed more easily, even in ecological swimming conditions, but few studies have been conducted in swimming-pool conditions with portable breath-by-breath telemetric systems. An inverse relationship exists between the velocity corresponding to VO2max and the time a swimmer can sustain it at this velocity. The energy cost of swimming varies according to its association with velocity variability. As, in the end, the supply of oxygen (whose limitation may be due to central—O2 delivery and transportation to the working muscles—or peripheral factors—O2 diffusion and utilization in the muscles) is one of the critical factors that determine swimming performance, VO2 kinetics and its maximal values are critical in understanding swimmers` behavior in competition and to develop efficient training programs.